2014
DOI: 10.1080/01932691.2014.911105
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Application of New Polycarboxylate Superplasticizers with Mild Retarding Performance Based on Monovinyl β-Cyclodextrin Monomer

Abstract: Based on monovinyl b-CD monomer (GCD), random copolymers (PTCDs) were first synthesized by AA, TPEG, and GCD, and characterized by FTIR and GPC. The application performances of PTCDs as superplasticizers in cement and concrete were investigated considering dispersion, adsorption, setting times, and compressive strength. The results indicated that PTCDs had more excellent applied performance compared with AA-co-GCD copolymers, and the outstanding feature is that PTCDs had a mild tunable retarding effect. When w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…It is a cyclic oligosaccharide and has hydrophilic outer surface and hydrophobic inner cavity. Recently, some researchers had applied β ‐CD in the modification of PCE to lower the clay sensitivity and obtain a better dispersing performance for cement 22–24 . For example, Xu modified TPEG‐type PCE with β‐CD, and then tested its clay tolerance property by measuring the fluidity of cement paste as adding Ca‐montmorillonite.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a cyclic oligosaccharide and has hydrophilic outer surface and hydrophobic inner cavity. Recently, some researchers had applied β ‐CD in the modification of PCE to lower the clay sensitivity and obtain a better dispersing performance for cement 22–24 . For example, Xu modified TPEG‐type PCE with β‐CD, and then tested its clay tolerance property by measuring the fluidity of cement paste as adding Ca‐montmorillonite.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some researchers had applied β-CD in the modification of PCE to lower the clay sensitivity and obtain a better dispersing performance for cement. [22][23][24] For example, Xu modified TPEG-type PCE with β-CD, and then tested its clay tolerance property by measuring the fluidity of cement paste as adding Ca-montmorillonite. The results showed that the fluidity of cement paste was considerably increased.…”
Section: Introductionmentioning
confidence: 99%
“…The wide expansion of CDs was made possible by their low-cost production on an industrial scale. CD-based polymers, in which the CDs are covalently grafted on a polymeric backbone, have found interesting applications as a concrete water-reducing agent [also named as superplasticizers (SPs)]. SPs play a crucial role in modern concrete technology because they guarantee good fluidity of cement pastes and control their setting time, even at low water/cement ratios. Among the SPs of first generation, the sulfonated additives such as poly-β-naphthalene sulfonate (SNF) and polymelamine sulfonate (SMF) have found wide applications. Polycarboxylate ether (PCE) SPs show superior performance in cement-based mortars.…”
Section: Introductionmentioning
confidence: 99%
“…In the past years, increasing attention has been devoted to designing ecofriendly SPs, and among them, β-CD-based dispersants have been playing a crucial role. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation